2014
DOI: 10.4137/ijtr.s16800
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Kynurenine Pathway in Schizophrenia

Abstract: Several studies suggest a role for kynurenic acid (KYNA) in the pathophysiology of schizophrenia. It has been proposed that increased brain KYNA levels in schizophrenia result from a pathological shift in the kynurenine pathway toward enhanced KYNA formation, away from the other branch of the pathway leading to quinolinic acid (QUIN). Here we investigate the levels of QUIN in cerebrospinal fluid (CSF) of patients with schizophrenia and healthy controls, and relate those to CSF levels of KYNA and other kynureni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 42 publications
7
68
0
1
Order By: Relevance
“…The functional overweight of astrocytes may lead to a further accumulation of KYNA [37]. Indeed, a study referring to the expression of IDO and TDO in schizophrenia showed exactly the expected results.…”
Section: Inflammation In Schizophrenia Is Associated With Changes Ofsupporting
confidence: 49%
“…The functional overweight of astrocytes may lead to a further accumulation of KYNA [37]. Indeed, a study referring to the expression of IDO and TDO in schizophrenia showed exactly the expected results.…”
Section: Inflammation In Schizophrenia Is Associated With Changes Ofsupporting
confidence: 49%
“…Although the effects of kynurenine, a neurotoxic Glu agonist, have been studied extensively in MDD, additional research has demonstrated that an imbalance of the kynurenine pathway is also common to SCH, AD and PD (Gong et al, 2011;Kegel et al, 2014;Zinger et al, 2011). Therefore it is reasonable to hypothesize that following PA enhanced skeletal muscle-mediated conversion of the neurotoxin kynurenine, which is capable of crossing the BBB, to kynurenic acid, a compound which does not readily cross the BBB (Olah et al, 2013), could be beneficial in regulating diseases other than MDD.…”
Section: Summary and Hypothesesmentioning
confidence: 99%
“…It is hypothesized that increased conversion of tryptophan to kynurenic acid by astrocytes leads to inhibition of N-methyl-d-aspartate (NMDA) receptors and results in hypoglutamatergic neurotransmission in schizophrenia. 9 Kynurenate is also toxic to oligodendrocytes via an as yet undefined mechanism that is unrelated to NMDA 42 and may therefore contribute to demyelination processes in schizophrenia. The kynurenine pathway constitutes a promising target for novel antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…T gondii infection and schizophrenia both involve increased production of L-kynurenine and its metabolites affecting glutamate receptor signaling and neuro-excitotoxicity. [8][9][10] T gondii infection and schizophrenia also both manifest significant neuroinflammation [11][12][13][14][15][16][17] and disregulation of neurotransmitters, particularly dopamine and serotonin. [18][19][20][21] Additionally, several reports have documented the ability of T gondii to alter rodent neural connectivity 22 and fear behavior, 23,24 and influence human behavior (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%